Proses Komunikasi dalam City Branding melalui Budaya Musik Saronen Di Sumenep Madura - Mohammad Insan Romadhan (Universitas Muhammadiyah Sidoarjo, 2018)
Nowadays, the globalization era makes the tourism industry got the impact of globalization. The city is as destination that become one of the components can can attract tourists. An interesting phenomenon arises that there are many kinds of cities with various tagline. One of them is The Soul of Madura. Based on the city branding processin Sumenep city, thus representation should be concerned through branding that will be done, branding process that is done requires communication, because communication is one of branding process that is done. Besides, the researcher wants to see how the communication process in the saronen music culture in the process of branding. This research used a qualitative approach in the type of descriptive research. The object in this research was saronen music culture. The result was a communication that is created in the process of city branding at saronen music culture. It included all conceptulization, even they were one-way communication processes, interactions and transactional processes.